Fear of Missing Out as a Predictor of Digital Fatigue: A Correlational Study Among Indonesian Youth - Adissah Putri Herdianti; Mardianto (IJIP : Indonesian Journal of Islamic Psychology, 2025)
The digitalization era has reshaped how individuals communicate and interact, yet it has also intensified psychological strains such as digital fatigue. Fear of Missing Out (FoMO); the anxiety of being excluded from rewarding social experiences has been identified as a potential psychosocial mechanism underlying this phenomenon. This study examined the predictive role of FoMO on digital fatigue among Indonesian digital natives using a correlational quantitative design. A total of 1,330 participants aged 13–30 years were recruited through stratified convenience sampling across western, central, and eastern Indonesia. Data were collected using the modified and culturally adapted Online Fear of Missing Out Inventory (15 items) and Digital Fatigue Scale (14 items), both validated through confirmatory factor analysis and showing high reliability (α = 0.91–0.92). Regression analysis indicated that FoMO significantly predicted digital fatigue (β = 0.582, SE = 0.021, p < 0.001), explaining 33.8% of the variance. These findings suggest that FoMO functions as a central psychological mechanism linking unmet social relatedness needs with cognitive overload and emotional exhaustion. The study extends digital psychology by integrating motivational and cognitive frameworks within a collectivistic cultural context and provides empirical support for digital wellness interventions emphasizing self-regulation, emotional awareness, and culturally adaptive literacy programs among Indonesian youth.